Empowerment of Fisherman Wives through Promotion of Mangrove Processed MSMEs at the Petik Laut Festival, Cemara Beach, Jember District - Wahyuni, Lilik; Sholihah, Qomariyatus; Kholifah, Siti; Galisong, Ridwan Danuarta; Arifin, Nur Hikmah; Arifin, Aprilina (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2024)
This study aims to empower fishermen's wives through the promotion of micro, small, and medium enterprises (MSMEs) focusing on processed mangrove products at the Petik Laut Festival, Cemara Beach, Jember. The research method used is a mixed approach that includes observation, focus group discussion (FGD), and matrix of cross-impact multiplications applied to a classification (MICMAC) analysis. The results of the study indicate that market access, financial literacy, and social networks are key factors in the success of coastal women's economic empowerment. The Petik Laut Festival has proven to be effective in promoting processed mangrove products, expanding market reach, and increasing the competitiveness of local products when viewed from market access. Therefore, it is important to develop women's capacity through entrepreneurship education and access to technology. This empowerment supports poverty alleviation and gender equality, in line with the Sustainable Development Goals (SDGs). Further research is needed to assess the long-term impact of this empowerment strategy.